2017
DOI: 10.21548/38-1-837
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Approach for Understanding the Haze Phenomenon in Bottled White Wines at Molecular Level

Abstract: The stabilisation of the proteinaceous material in the wine matrix represents one of the big challenges for the production of quality white wines, but the characterisation of the mechanism that governs the interactions between its components is still a very challenging goal. The aim of this study was to provide new information for developing new technologies in the stabilisation of bottled white wines using a novel theoretical approach. This method combines electronic structure calculations for the determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In the presence of polyphenolic compounds, HUPs with lower proline content showed a lower or complete absence of turbidity in model systems, which might result from less proline–phenolic-binding sites . Such phenolic-binding sites have already been reported in a cleft located between the domains I and II of certain TLPs. , Other protein secondary structure elements such as loops in the TLPs can unfold upon heating and become prominent on the protein surface, exposing binding sites for phenolic compounds. , …”
Section: Origin Of Wine Hazementioning
confidence: 96%
See 1 more Smart Citation
“…In the presence of polyphenolic compounds, HUPs with lower proline content showed a lower or complete absence of turbidity in model systems, which might result from less proline–phenolic-binding sites . Such phenolic-binding sites have already been reported in a cleft located between the domains I and II of certain TLPs. , Other protein secondary structure elements such as loops in the TLPs can unfold upon heating and become prominent on the protein surface, exposing binding sites for phenolic compounds. , …”
Section: Origin Of Wine Hazementioning
confidence: 96%
“…Wine haze is not promoted by any particular singular factor but rather by a combination of haze inducing elements and physicochemical conditions, which result in protein aggregation. ,, These factors include the (in)­stability of different HUP isoforms, pH, ionic strength, temperature and concentration of phenolic compounds, sulfite ions, and polysaccharides. , …”
Section: Origin Of Wine Hazementioning
confidence: 99%
“…These values indicate that VVTL1 is a hydrophilic stable protein [41,42]. Moreover, this protein is characterized by a relative rigid structure due to the presence of the eight disulphide bonds [24] that, alongside with its hydrophilicity, should not favor its interaction with polyphenols, even if it has been reported that the protein possesses a pocket with high hydrophobicity that could host/bind small polyphenols as quercetin and caffeic acid [26].…”
Section: Polyphenols-vvtl1 Interactionsmentioning
confidence: 98%
“…VVTL1 isoforms all have three structural domains (a central core flanked by two domains, Figure 1A) and eight disulphide bridges, which give stability to the structure [24]. These proteins present surface areas that are characterized by different hydrophobicity (Figure 1B and 1C) and electrostatic potentials ( Figure 1A), and show an acidic cleft (see arrow in Figure 1A), in which small molecules, such as phenolics, can be accommodated [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, protein instability does not correlate with total protein concentration because individual proteins behave differently (Bayly and Berg, 1967;Hsu and Heatherbell, 1978). In addition, the chemical composition of the wine (for example, metal ions, ionic strength, pH, alcohol content, polysaccharides and phenolic content) may also play an important role in protein haze formation as these parameters could affect protein denaturation (Waters et al, 1995;Muhlack et al, 2016;Toledo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%